Building leadership capacity in women: an NGO in India's initiative towards women members of SHGs. Issue 7 (2nd October 2020) - Bryan, Venise; Mendaglio, Salvatore
ABSTRACT: Many NGOs in India strive to empower women to lead through various programmes, but their effectiveness in the participants' lives is not known. This article reports on a descriptive cross-sectional study that used authentic leadership theory to explore an NGO's self-help group programme's ability to empower women by building their leadership capacity and self-efficacy to lead. Participants reported an increased capacity and self-efficacy to lead in their daily lives. Women who were in the programme for a longer period reported greater self-efficacy to lead, as compared to those who recently joined, showing the significance of women's empowerment programmes.